Developing a framework for Green Curriculum in higher culinary education - Ratna Palupi Nurfatimah; Diwyacitta Antya Putri; Luthfiyah Nurlaela; Sri Handajani; Mauren Gita Miranti; Annisa Nur'aini; Hanif Naufal Ahmi; Mohd Yusof Bin Kamaruzaman (LPMPP Universitas Negeri Yogyakarta, 2026)
The accelerating global environmental crisis demands the integration of sustainability within higher culinary education. This study aims to analyze the implementation of the Green Curriculum (GC) framework at Universitas Negeri Surabaya (UNESA) and Universiti Pendidikan Sultan Idris (UPSI). Utilizing a qualitative content analysis with simple frequency quantification involving 50 participants, the findings reveal that implementation is in a transitional phase marked by three fundamental gaps. First, a significant gap exists between the high level of philosophical awareness among internal stakeholders and the lack of systemic action, despite new demands for sustainability competencies. Second, implementation is critically impeded by the university support system; infrastructure ('Facilities & Infrastructure,' f=84) was the most frequent concern, creating a 'hidden curriculum' conflict in which poor facilities (e.g., wastewater treatment) contradict pedagogical goals. Third, the framework is overwhelmingly inward-looking, rendering the community participation pillar the least emphasised (frequency <2%). This research concludes that achieving a mature GC requires a radical shift from conceptual adoption to tangible systemic alignment, prioritizing investment in critical infrastructure and the institutionalization of external partnerships for holistic operational reality.